2017
DOI: 10.1128/jvi.00391-17
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-associated Virus (AAV) Serotypes Have Distinctive Interactions with Domains of the Cellular AAV Receptor

Abstract: Adeno-associated virus (AAV) entry is determined by its interactions with specific surface glycans and a proteinaceous receptor(s). Adeno-associated virus receptor (AAVR) (also named KIAA0319L) is an essential cellular receptor required for the transduction of vectors derived from multiple AAV serotypes, including the evolutionarily distant serotypes AAV2 and AAV5. Here, we further biochemically characterize the AAV-AAVR interaction and define the domains within the ectodomain of AAVR that facilitate this inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
161
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(172 citation statements)
references
References 57 publications
6
161
0
Order By: Relevance
“…Although there is no observable role for AAVR in the cellular attachment of AAV4 and AAVrh32.33, we wanted to determine whether these vectors are able to bind to AAVR even if they are unable to functionally engage it for cellular entry. We used a previously reported virus overlay assay (34,46) to interrogate the binding of AAV4 to purified AAVR or AAVR expressed in cell lysates. The AAV4 virus overlay on purified AAVR domains illustrates that under the same conditions as those that demonstrated AAV2 binding to AAVR, no detectable binding of AAV4 to AAVR PKD1, PKD2, PKD3, or PKD1-5 is observed (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is no observable role for AAVR in the cellular attachment of AAV4 and AAVrh32.33, we wanted to determine whether these vectors are able to bind to AAVR even if they are unable to functionally engage it for cellular entry. We used a previously reported virus overlay assay (34,46) to interrogate the binding of AAV4 to purified AAVR or AAVR expressed in cell lysates. The AAV4 virus overlay on purified AAVR domains illustrates that under the same conditions as those that demonstrated AAV2 binding to AAVR, no detectable binding of AAV4 to AAVR PKD1, PKD2, PKD3, or PKD1-5 is observed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently a multiserotype AAV receptor (AAVR) was identified by using an unbiased genome-scale genetic screen (33). AAVR directly interacts with AAV particles via Ig-like polycystic kidney disease (PKD) domains present in the ectodomain of AAVR (33,34). It is required for the efficient transduction of multiple AAV serotypes (AAV1, -2, -3B, -5, -6, -8, and -9) in all cell lines that were tested.…”
mentioning
confidence: 99%
“…The AAVR was shown to play an essential role in infection by multiple AAV serotypes (including AAV1, AAV2, AAV3b, AAV5, AAV6, AAV8 and AAV9) with respect to mediating rapid endocytosis from the plasma membrane and trafficking to the trans‐Golgi network. Subsequent work showed that AAVR is an N‐linked glycosylated membrane protein using the host cell endosomal pathway to cycle between the plasma membrane and the trans‐Golgi network . The finding of N‐linked glycosylation on the AAVR opens the possibility that it may function during both the initial attachment and the secondary internalization of AAV9 capsids.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent work showed that AAVR is an N-linked glycosylated membrane protein using the host cell endosomal pathway to cycle between the plasma membrane and the trans-Golgi network. 32 The finding of N-linked glycosylation on the AAVR opens the possibility that it may function during both the initial attachment and the secondary internalization of AAV9 capsids. This potential duality of function in the AAVR may help explain why ischemia and desialylation have such dramatic impacts on the efficiency of AAV9-mediated gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Other parvoviruses and adeno-associated viruses (AAV) use a variety of different receptors for binding and infection of cells. The AAVs use a protein receptor (the AAV receptor), which they bind through different domains, in addition to a variety of other glycoprotein or glycan receptors, including heparin sulfate proteoglycans and sialic acids (49)(50)(51). Those distinct interactions determine the tissue tropism of the AAVs and the gene delivery vectors derived from them (52).…”
mentioning
confidence: 99%